Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1590/s1519-566x2011000600007
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of the midgut of Melipona quadrifasciata anthidioides (Lepeletier) (Hymenoptera: Apidae) during metamorphosis

Abstract: In Hymenoptera, midgut changes begin in the last instar. At this stage, the larval epithelial digestive cells degenerate, leaving only the basal membrane and the regenerative cells which will develop into a new epithelium during the pupal stage and in the adult. Epithelium renewal is followed by changes in volume and shape of the midgut. Morphometric analysis of digestive cells and total midgut volume of Melipona quadrifasciata anthidioides (Lepeletier) were conducted to verify whether cell volume increase are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
2
14
0
2
Order By: Relevance
“…The proliferation of regenerative cells, in turn, as observed in the present study, had already been reported in the midgut of larvae, pre-pupae and pupae of M. quadrifasciata (Martins et al 2006;Cruz et al 2011Cruz et al , 2013. The analyses carried out confirmed that regenerative cells in bees initiate the differentiation process and the formation of digestive cells in the pre-pupal stage (Neves et al 2003a, b).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The proliferation of regenerative cells, in turn, as observed in the present study, had already been reported in the midgut of larvae, pre-pupae and pupae of M. quadrifasciata (Martins et al 2006;Cruz et al 2011Cruz et al , 2013. The analyses carried out confirmed that regenerative cells in bees initiate the differentiation process and the formation of digestive cells in the pre-pupal stage (Neves et al 2003a, b).…”
Section: Discussionsupporting
confidence: 89%
“…The midgut of insects is the main organ responsible for food digestion and the absorption of nutrients. In the midgut epithelium, including that of bees, there are three major cell types: endocrine cells, which produce and secrete peptides with endocrine functions; digestive cells, which perform the digestion and absorption of food; and regenerative cells or stem cells, responsible for cell renewal and remodelling of the epithelium (Serrão and Cruz-Landim 1996;Martins et al 2006;Malaspina and Silva-Zacarin 2006;Cruz et al 2007Cruz et al , 2011Nagy et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Midgut progenitor cells that differentiate into all types of the midgut epithelial cells have been described mainly for arthropods. They are described as cells which show the features of both midgut stem cells and digestive cells (Martins et al, 2005;Cruz et al, 2011;Chajec et al, 2012). The amount of reserve material (e.g.…”
Section: Discussionmentioning
confidence: 99%